2017
DOI: 10.1590/0100-5405/2160
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in the in vitro sensitivity oF Drechslera tritici-repentis, isolated from wheat, to strobilurin and triazole fungicides

Abstract: Reports of failure in the chemical control of wheat yellow leaf spot led to determination of the sensitivity of Drechslera tritici-repentis (Dtr) to the fungicides quinone outside inhibitors (QoIs) and demethylation inhibitors (DMIs). The IC50 was obtained for strobilurins (azoxystrobin, kresoxim-methyl, picoxystrobin and pyraclostrobin) and for triazoles (cyproconazole, epoxiconazole, propiconazole, prothioconazole and tebuconazole), using five Dtr isolates. Seven concentrations of the fungicides were tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 6 publications
(8 reference statements)
0
7
0
Order By: Relevance
“…In Brazil, tan spot is an important and severe disease of wheat, particularly in the southern region of the country. Tonin et al (2017) demonstrated that tan spot control failures in Brazilian fields with fungicide applications were due to a reduced sensitivity of Ptr isolates to both Qols and DMI fungicides. In the present study, a total of 82 Argentinian Ptr isolates were obtained from fields where tan spot control failure was reported, and assessed for in vitro sensitivity to three QoI fungicides.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Brazil, tan spot is an important and severe disease of wheat, particularly in the southern region of the country. Tonin et al (2017) demonstrated that tan spot control failures in Brazilian fields with fungicide applications were due to a reduced sensitivity of Ptr isolates to both Qols and DMI fungicides. In the present study, a total of 82 Argentinian Ptr isolates were obtained from fields where tan spot control failure was reported, and assessed for in vitro sensitivity to three QoI fungicides.…”
Section: Discussionmentioning
confidence: 99%
“…The higher fungitoxic capacity of pyraclostrobin compared to other QoI fungicides has already been demonstrated for various pathogens including Ptr. For example, Tonin et al (2017) and Abdullah (2017) reported that among all the QoI fungicides evaluated against Ptr, pyraclostrobin was the most fungitoxic. These researchers did not find an explanation for these differences between molecules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plots treated with the mixtures, without addition of mancozeb, showed severity of 18% for epoxiconazole + pyraclostrobin, 26% for fluxapyroxad + pyraclostrobin, 28% for epoxiconazole + kresoxim methyl, 34% for prothioconazole + trifloxystrobin, 34 % for azoxystrobin + propiconazole, 39% for cyproconazole + picoxystrobin, and 62% for azoxystrobin + benzovindiflupyr ( Table 1). The high severity after treatments, without addition of the protectant, evidences the difficulty in controlling leaf blights with these mixtures (10,12). This shows the reduction in sensitivity of D. tritici-repentis to DMIs + QoIs, and QoI + SDHI.…”
Section: Resultsmentioning
confidence: 99%
“…Mean control of wheat leaf blights has been less than 50%. Such low efficiency indicates that the fungicide application cost is not covered and has a negative effect on wheat grain yield (10).…”
Section: Introductionmentioning
confidence: 99%